Augmented Reality in Elementary School IPAS Learning: A Bibliometric Analysis and Systematic Review - Salsabila Aziz; Chairul Amriyah; Yudesta Erfayliana (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
This study examines the urgency of technological innovation in addressing the challenges of visualizing abstract concepts in Natural and Social Sciences (IPAS) subjects in elementary schools, particularly within the context of the Independent Curriculum. The focus of this study is to map Augmented Reality (AR) research trends during the 2018–2025 period to identify scientific evolution and future strategic development opportunities. This study screened 27 high-quality articles from the Scopus database using a systematic literature review (SLR) approach that follows the PRISMA protocol, combined with bibliometric analysis via VOSviewer. The research findings show (1) Publication Surge: There has been an exponential increase in AR research post-2020. (2) Pedagogical Effectiveness: AR has been proven significant in improving cognitive learning outcomes and intrinsic motivation through project-based inquiry approaches and personalized learning. (3) Asian countries dominate the research landscape, collaborating across disciplines in reputable journals (Q1). Although AR has the potential to transform the understanding of integrative concepts in IPAS (Integrated Physical and Applied Sciences), there are still gaps in longitudinal study designs and challenges in technology accessibility in rural areas. The results of this study provide a strong foundation for the development of a curriculum based on cutting-edge pedagogy and serve as a catalyst for inclusive education research to strengthen the profile of adaptive and innovative Pancasila students.